180k views
1 vote
7(p + 3) + 9 = 5(p – 2) – 3p

User Sunand
by
6.5k points

2 Answers

3 votes

Answer:

p = -8

Explanation:

step 1

((7•(p+3))+9)-(5•(p-2)-3p) = 0

step 2

(7 • (p + 3) + 9) - (2p - 10) = 0

step 3

5p + 40 = 5 • (p + 8)

step 4

5 • (p + 8) = 0

5 = 0 (This equation has no solution)

step 5

p+8 = 0

p = -8 (This is the answer)

User Annie Kim
by
5.4k points
0 votes

Answer:


p=-8

Explanation:


7(p + 3) + 9 = 5(p - 2) - 3p\\

1. distribute


7p +21 +9 = 5p -10 - 3p\\

2. collect like terms


21+9+10 = 5p - 3p - 7p

3. solve


40 = -5p\\-8 = p

User Stvar
by
6.3k points